Portal hypertension and reactive hemophagocytosis in pediatric visceral leishmaniasis - Das, Suman; Sarkar, Nirmalya; Chatterjee, Kaushani; Aich, Bholanath; Bhattacharya, Mala (Bangladesh Journal of Medical Science, 2015)
A 10 year old boy suffering from prolonged low grade fever, progressive pallor, one episode of haematemesis and melaena, was found to have hepatospenomegaly, features of portal hypertension on abdominal ultrasound, and grade II varices in upper gastrointestinal endoscopy. During hospital stay for diagnostic workup, he developed features of hepatic failure and pancytopenia. Bone marrow aspirate revealed hemophagocytosis and plenty of Leishman-Donovan bodies. The child received Injection Sodium Stibogluconate to treat leishmaniasis and received supportive therapy for hepatic failure and pancytopenia. The child responded well to treatment. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.409-412